Detection of Antibiotic Resistance among Gram-Negative Bacteria Isolated from Urinary Tract Infections - Aya Talib jawad,; Saadon, Hanan; Sarah Ghalib Khudhur,; Hussein Adnan Obaid,; Hamzah Shakir,; Salman , Noor Abd Alkhudhur; Al-Ali , Hayat Asa’ad (University of Thi-Qar Journal of Science, 2024)
This study showed all isolates of bacteria are identified by many testes , such as morphological, biochemical, and API20E testes, as,  the results confirmed that the Gram-negative bacteria in Thi-Qar government during the period of June and July 2023-2024. A total of 60 non-duplicate urine samples from patients are collected and examined for detection of Gram-negative bacteria. The results show that out of 60 urine samples 35(58.33%) samples are positive for bacterial growth of Gram negative. The results of bacterial diagnosis depending on testing showed that the frequency of bacterial pathogens thatause UTI as the following 15 (42.85%) are Escherichia coli,7 (20.0%) Enterobacter cloacae, 5 (14.28%) Klebsiella pneumonia, 3 (8.57 %) are from each of Proteus mirabilis and Pseudomonas aeruginosa, and 2 (4.76%) are Citrobacter spp.  Antibiotics were divided into three categories that work on (nucleic acid, protein inhibition ,and bacterial cell wall synthesis) and the three groups were compared with each other .It was concluded which of them was more effective and performed better in eliminating bacteria and the results appeared as follows: Gram negative bacteria showed 91.42 % resistance to ampicillin 85.7% resistance to amikacin, 65.71% resistance to levofloxacin, 45.71% resistance to Norfloxacin, 31.42 % resistance to azithromycin and 13.37% resistance to ciprofloxacin.